1982
DOI: 10.1111/j.1365-3083.1982.tb00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Murine Immune Responses to Orally Administered Haptenated Streptococcus mutans

Abstract: The induction of immune responses to orally administered trinitrophenyl (TNP)-haptenated Streptococcus mutans and its enhancement with muramyldipeptide (MDP), peptidoglycan (PG), and concanavalin A (Con A) were investigated in lipopolysaccharide (LPS)-non-responsive C3H/HeJ mice and the syngeneic, LPS-responsive C3H/HeN strain. Both mouse strains manifested similar immune responses, primarily of the IgM isotype, after a single gastric intubation (GI) with TNP-S. mutans. However, when groups of animals were fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the study reported here, we have shown that the oral administration of particulate S. mutans antigens with either MDP or S. mutans CW-derived PG results in enhanced salivary IgA anti-S. mutans antibody levels. This finding was not totally unexpected since we have previously shown that the oral administration of trinitrophenyl (TNP)-haptenated S. mutans and either MDP or PG to mice results in enhanced anti-TNP plaque-forming-cell and antibody responses (14). Furthermore, it is well known that MDP exhibits adjuvant properties for a number of antigens when administered by the oral route (3).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In the study reported here, we have shown that the oral administration of particulate S. mutans antigens with either MDP or S. mutans CW-derived PG results in enhanced salivary IgA anti-S. mutans antibody levels. This finding was not totally unexpected since we have previously shown that the oral administration of trinitrophenyl (TNP)-haptenated S. mutans and either MDP or PG to mice results in enhanced anti-TNP plaque-forming-cell and antibody responses (14). Furthermore, it is well known that MDP exhibits adjuvant properties for a number of antigens when administered by the oral route (3).…”
Section: Discussionmentioning
confidence: 77%
“…Since PG is a major component of the S. mutans CW, we considered the possibility that adjuvant derivatives from this structure could be used in an oral vaccine against dental caries. Our previous studies (14) have indicated that the oral administration of PG with haptenated S. mutans to mice enhanced splenic plaque-forming-cell responses, especially of the IgA isotype. Therefore, in the next series of experiments, gnotobiotic rats were given S. mutans 6715 WC or purified CW either alone or together with purified S. mutans PG by GI.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Effective immunity against dental caries in rats, obtained after oral administration of S. mutans (14), is generally associated with the presence in saliva of antibodies directed against several cell wall components, including lipoteichoic acids, serotype polysaccharide, and cell wall proteins (12,18). However, immunity and protection are not restricted to vaccination with whole bacteria, and proteins or polysaccharides could act as active antigens in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of T cell dependent (TD) antigens such as SRBC or whole bacteria results in Th cell induction in PP [45,471 and in subsequent IgA responses in spleen and in external secretions [45,47,62]. Furthermore, purified Th cells from PP of mice given antigen by the oral route, when added to normal splenic B cell cultures and immunized with the homologous oral-priming antigen, support IgM, IgG and mainly IgA responses [47] ( Table I).…”
Section: Fcr+ Th Cells and Ig Bf Regulation Of The Iga Responsementioning
confidence: 99%